Early ficolin-1 is a sensitive prognostic marker for functional outcome in ischemic stroke. Issue 1 (December 2016) - Zangari, R.; Zanier, E.; Torgano, G.; Bersano, A.; Beretta, S.; Beghi, E.; Casolla, B.; Checcarelli, N.; Lanfranconi, S.; Maino, A.; Mandelli, C.; Micieli, G.; et al.
Abstract Background Several lines of evidence support the involvement of the lectin pathway of complement (LP) in the pathogenesis of acute ischemic stroke. The aim of this multicenter observational study was to assess the prognostic value of different circulating LP initiators in acute stroke. Methods Plasma levels of the LP initiators ficolin-1, -2, and -3 and mannose-binding lectin (MBL) were measured in 80 stroke patients at 6 h only and in 85 patients at 48 h and later. Sixty-one age- and sex-matched healthy individuals served as controls. Stroke severity was measured on admission using the National Institutes of Health Stroke Scale (NIHSS). The outcome was measured at 90 days by the modified Rankin Scale (mRS). Results Ficolin-1 was decreased in patients compared with controls measured at 6 h (median 0.13 vs 0.33 μg/ml, respectively, p  < 0.0001). At 48 h, ficolin-1 was significantly higher (0.45 μg/ml, p  < 0.0001) compared to the 6 h samples and to controls. Likewise, ficolin-2 was decreased at 6 h (2.70 vs 4.40 μg/ml, p  < 0.0001) but not at 48 h. Ficolin-3 was decreased both at 6 and 48 h (17.3 and 18.23 vs 21.5 μg/ml, p  < 0.001 and <0.05, respectively). For MBL no difference was detected between patients and controls or within patients at the different time points. In multivariate analysis, early ficolin-1 was independently associated with unfavorable mRS outcome (adjusted odds ratio (OR): 2.21, confidence interval (CI) 95 % 1.11–4.39, p  = 0.023). Early ficolin-1 improved the discriminating ability of an outcome model including NIHSS and age (area under the curve (AUC) 0.95, CI 95 % 0.90–0.99, p  = 0.0001). Conclusions The ficolins are consumed within 6 h after stroke implicating activation of the LP. Early ficolin-1 is selectively related to 3-month unfavorable outcome.